The Relationship Between Latent Myofascial Trigger Point and Range of Motion of Knee Flexor and Extensor Muscles - Das, Rajdeep; Jhajharia, Birendra; Ciocan, Vasile Catalin; Majumdar, Indu; Sharma, Arnav (Physical Education Theory and Methodology, 2023)
The study purpose was to assess the relationship between Latent Myofascial Trigger Point and range of motion in the lower limb of athletes. A lower Pain pressure threshold (< 25 lbs/cm2) in muscles indicates the presence of a latent myofascial trigger point. Materials and methods. Initially, the study involved 46 male Athletes (aged 20-23 years) as participants. The pain pressure threshold was measured by the pressure algometer (FPX 25 Wagner Instruments, Greenwich, CT, USA) to detect latent myofascial trigger points on the hamstring and quadriceps muscles. Out of 46 participants, 23 tested positive with a latent myofascial trigger point, and rest of them tested negative with a latent myofascial trigger point. All the participants measured knee flexor and extensor range of motion with the Kinovea software (version 0.9.5). In descriptive statistics, mean and standard deviation were used, and Pearson correlation was used to determine the relationship between the variables. The level of significance was set at 0.05. Results. A significant correlation was found between Latent Myofascial Trigger Points and lower limb range of motion (p < 0.05), and it was also observed that the magnitude of correlation coefficient was very large (0.7–0.9). Conclusions. Latent Myofascial Trigger Points impair sports performance by decreasing the range of motion of knee flexors and extensors. In light of this, Latent Myofascial Trigger Point should be considered a serious musculoskeletal disorder, and appropriate preventative measures should be taken by health professionals.